Ethnopharmacology and Computer-Aided Tandem Protocol to Search for Antimalarial Agents from Indonesian Medicinal Plants: HAP Inhibitor - Adinda Kusuma Pertiwi; Muhammad Habiburrohman; Yoshinta Debby; Bawon Triatmoko; Ari Satia Nugraha (Nusantara Science and Technology Proceedings)
The anti-malarial potency of Indonesian medicinal plants was evaluated through computational study. From 43 Indonesian medicinal plants, 238 previously reported compounds were carefully docked into HAP (histo-aspartic protease) with codename 3FNT in which the enzyme plays an important catalytic role in Plasmodium falciparum innate metabolism. Exhaustive docking experiments produced 6 best hits molecules including AM210 (4-hydroxy- 3-methoxy strychnine), AM213 (protostrychnine), and AM216 (pseudostrychnine) which have less free energy compared to HAP native ligand, 1,2-ethanediol. This study revealed the potency of Strychnos nux-vomica L. as a source for antimalaria and support its traditional claims.